Isolasi dan Karakterisasi Flavonoid dari daun sambang darah (Excoecaria cochinchinensis L) - Siska Oktariza; Yustini Ma’aruf; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2013)
Flavonoids are greatest a group of phenolic compounds found in nature. One of the plants that contain flavonoids and used as medicine are the leaves sambang darah (excoecaria cochichinensis L). This study aims to isolate and characterize flavonoids from leaves sambang darah (excoecaria cochichinensis L). The method used is maceration using solvents methanol and fractionation with n-hexane and ethyl acetate. Separation was performed by column chromatography with silica gel 60 adsorbent and eluent ethyl acetate: methanol in SGP (Step Gradient Polarity) and recrystallization purification done. From the results obtained by the isolation of flavonoids in the form of brownish yellow solid, it has not obtained pure of flavonoids.